tudying the Relationship between the Lund Mackay Score and Response to Medical Treatment in Patients with Chronic Sinusitis - Gholam-Ali Dashti Khavidaki1 , Reza Gharibi1 (Institute of Medico-legal Publications Pvt Ltd, 2021)
The present study was conducted to investigate the relationship between the Lund Mackay score andresponse to medical treatment in patients with chronic sinusitis. The present study was performed crosssectionally on 150 patients referred to Khatam-ul-Anbia Hospital in Zahedan for whom the diagnosis ofchronic sinusitis was confirmed and met the study criteria. Demographic data and clinical signs of patientswere recorded and for based on CT scan, The Lund Mackay score was evaluated. Patients were treated for 4to 6 weeks and finally re-evaluated for symptoms and response to treatment. Data were analyzed using SPSSsoftware version 24, McNemar test, Mann-Whitney and other necessary tests for descriptive statistics. Asignificance level of 0.05 was considered. 3.55% of patients were male (83 patients) and 7.44% were female(67 patients). The mean score of the Lund Mackay in the present study was 92.11 with a standard deviationof 2.3. Symptoms of olfactory dysfunction, sinus pain, nasal obstruction and nasal discharge showedsignificant improvement after treatment (p <05.0). Based on the results obtained at the end of the study, thepresence of nasal polyps (p = 001.0) and nasal obstruction (p = 003.0), after the end of the treatment period,showed a significant relationship with the response to treatment. In general, this study suggested that themean score of The Lund Mackay had a significant positive relationship with the severity of patients’ clinicalsymptoms and the severity of sinusitis. Therefore, it can be considered as a suitable criterion in diagnosticand therapeutic evaluations of patients.